2016
DOI: 10.1108/ijwbr-08-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Causes and effects of wine tourism development in wineries

Abstract: Purpose This study aims to propose that the institutional environment exerts pressure on the behavior of wineries toward wine tourism development (WTD) and the effect of this influence confers legitimacy to the business of wine tourism. Design/methodology/approach Structural equation modeling through partial least squares was applied to estimate and validate a model using data from a quantitative survey in the universe of 62 wineries with a wine tourism component along the Alentejo Wine Route in Portugal. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 61 publications
(105 reference statements)
0
29
0
1
Order By: Relevance
“…The more institutionally organized a field is, the greater the effect that professional organizations, as purveyors of legitimacy, have over the industry. This can be carried out through the shaping of industry discourses (Greenwood et al, ; Scott, ), the ways in which firms interact with each other internationally (Buchanan & Marques, ; Chizema & Buck, ) and the ways in which firms are expected to develop internally (Lavandoski et al, ). Industry associations have been regarded as important institutional actors in industries, markets, and organizational fields (Barley, ; Rajwani, Lawton, & Phillips, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The more institutionally organized a field is, the greater the effect that professional organizations, as purveyors of legitimacy, have over the industry. This can be carried out through the shaping of industry discourses (Greenwood et al, ; Scott, ), the ways in which firms interact with each other internationally (Buchanan & Marques, ; Chizema & Buck, ) and the ways in which firms are expected to develop internally (Lavandoski et al, ). Industry associations have been regarded as important institutional actors in industries, markets, and organizational fields (Barley, ; Rajwani, Lawton, & Phillips, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…So how does this play out on‐the‐ground for organizations? Lavandoski et al () looked into how the institutional environment exerts pressure on wineries to develop wine tourism products in order to establish their legitimacy within the industry. They found that the prominent wine route organization and the national tourism entity were exerting normative and coercive pressures in the form of specific social requirements and legal regulations for the wine tourism products in wineries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if destinationoriented research remains a major theme in wine tourism, a notable change is the extent to which wine tourism and marketing-oriented studies have expanded from their historic base in Australia and New Zealand (Hall and Mitchell, 2008) to provide a much wider geographical coverage encompassing both New World (Bruwer and Joy, 2017;Singh and Hsiung, 2016) and Old World (Mauracher et al, 2016;Molina et al, 2015;Riguccio et al, 2017) wine-growing areas as well as emerging wine regions (Chong, 2017;Kerma and Ga cnik, 2015;Malm et al, 2013;Mazurkiewicz-Pizlo, 2016 Note: *Analysis conducted 27 August 2017 Table I. Journal articles on wine tourism in the Scopus database analysed by terms used in abstract, keywords and title Development concerns and issues remain a major theme in wine tourism research, with continuing interest in the life course of wine tourism at both operational and regional levels (Deery et al, 2012;Dodd and Beverland, 2016), although there remains a surprisingly limited amount of research on wine tourism business decision-making and strategy (Alonso et al, 2015;Lavandoski et al, 2016;Stavrinoudis et al, 2012) and issues of entrepreneurship (Dawson, Fountain and Cohen, 2011) and innovation (Alonso and Bressan, 2016;Baird and Hall, 2016). Growing attention is being given to the potential issues arising from increased tourism numbers in wine regions and the policy and planning issues that arise (Yelvington et al, 2014;Xu et al, 2016), although research on sustainability in a wine tourism context, as opposed to sustainable winegrowing, remains limited (Gázquez-Abad et al, 2015;Grimstad and Burgess, 2014).…”
Section: Johan Bruwer Editor-in-chiefmentioning
confidence: 99%